TNF-α − 308 G/A and IFN-γ + 874 A/T gene polymorphisms in Saudi patients with cutaneous leishmaniasis - Ahmed, Ahmed A.; Rasheed, Zafar; Salem, Tarek; Al-Dhubaibi, Mohammed S.; Al Robaee, Ahmad A.; Alzolibani, Abdullateef A. (BMC medical genetics, 2020)
Cutaneous leishmaniasis (CL) is well linked with immunogenetic factors. This study was undertaken to test the association of TNF-α - 308 and IFN-γ + 874 gene polymorphisms with the susceptibility of Leishmania (L) species among CL patients in central region of Saudi Arabia. This is a case-control study involved 169 Saudi subjects with different L. species and 199 healthy controls from central region of Saudi Arabia. All subjects were characterized by TNF-α - 308 G/A and IFN-γ + 874 A/T gene polymorphisms using PCR. Evaluation of genotyping and allelic frequency of TNF-α - 308 G/A in different L. species showed no significant association compared to controls (p > 0.05). Except, in cases of L. tropica that showed significantly higher TNF-α - 308 A versus G allele frequency (p = 0.0004). Evaluation of genotyping of IFN-γ + 874 (TT versus AA+AT recessive) and allelic frequency of IFN-γ + 874 (T versus A) showed significant higher in L. major and also in total CL cases as compared to healthy controls (p < 0.05). Furthermore, a strong association was observed between the susceptibility of L. major, L. tropica or total CL cases with synergistically combined high TNF-α 308/INF-γ 874 alleles. This is the first report that shows the gene polymorphisms of TNF-α - 308 G/A and IFN-γ + 874 A/T in Saudi patients with different L. species infections. Data showed that the TNF-α-308 G/A gene polymorphism is not associated with the susceptibility of CL in Saudi subjects. The only correlation was found in between A versus G allelic frequency in L. tropica. Importantly, IFN-γ + 874 A/T polymorphism was found to be associated with the susceptibility of L. major and also with total CL subjects. Moreover, data from synergistically combined high TNF-α 308/INF-γ 874 alleles strongly suggest their potential role in the susceptibility of leishmania infection.